1996
DOI: 10.1037/0096-1523.22.5.1166
|View full text |Cite
|
Sign up to set email alerts
|

Role of set in visual word recognition: Activation and activation blocking as nonautomatic processes.

Abstract: or dbesner@watarts. uwaterloo.ca. 1 We do not like the term semantic priming because it is associated with a particular mechanism thought to underlie the effect. Given that it has been used extensively throughout the literature we use it (reluctantly) to minimize misunderstanding.2 In Morton's (1969) conceptualization, a logogen contains no semantic or associative information and has no direct links to other logogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
149
7
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(167 citation statements)
references
References 51 publications
9
149
7
2
Order By: Relevance
“…In summary, these results suggest that semantic activation is critically modulated by the amount of attentional resources allocated to the prime word, and that auditory divided attention affects the processing from the word level to the semantic level, consistent with numerous studies of visual word recognition (e.g., Besner, Stolz, & Boutilier, 1997;Chiappe et al, 1996;Smith & Besner, 2001;Stolz & Besner, 1996). In addition, the difference in pattern between semantic priming and repetition priming permits us to reject other explanations for our results, such as the idea that the high divided-attention condition caused spreading activation to decay more rapidly than did the other conditions or that tone decision delayed target responding so that spreading activation from a fully activated prime word decayed prior to target responding.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In summary, these results suggest that semantic activation is critically modulated by the amount of attentional resources allocated to the prime word, and that auditory divided attention affects the processing from the word level to the semantic level, consistent with numerous studies of visual word recognition (e.g., Besner, Stolz, & Boutilier, 1997;Chiappe et al, 1996;Smith & Besner, 2001;Stolz & Besner, 1996). In addition, the difference in pattern between semantic priming and repetition priming permits us to reject other explanations for our results, such as the idea that the high divided-attention condition caused spreading activation to decay more rapidly than did the other conditions or that tone decision delayed target responding so that spreading activation from a fully activated prime word decayed prior to target responding.…”
Section: Discussionsupporting
confidence: 61%
“…Prior research has been interpreted to indicate that when attention is directed to the letter level of the prime word, priming is interrupted or modulated (Besner et al, 1990;Chiappe et al, 1996;Friedrich et al, 1991;Henik et al, 1983;Henik et al, 1994;Hoffman & MacMillan, 1985;Kahneman & Henik, 1981;Kaye & Brown, 1985;Marí-Beffa et al, 2000;Smith, 1979;Smith & Besner, 2001;Smith et al, 1996Smith et al, , 2000Smith et al, 1983;Stolz & Besner, 1996, 1998). An important contribution of our study is the suggestion that the influence of the amount of attentional resources used for the prime task is not limited to processing at the letter level: It must influence the processing of low-level features of words, thereby affecting the magnitude of semantic activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the word superiority effect (the better identification of letters in words than in nonwords) can be eliminated when participants know the position of the critical letter in advance and focus their attention there (Johnston & McClelland, 1974). Similarly Stroop interference can be reduced (Besner & Stolz, 1999) and there is no semantic priming (Stolz & Besner, 1996; when p articipants attend to individual letters (but see Mari-Beffe et al, 2000). Laberge (1983), using a probe detection procedure embedded in a reading task, further showed that attention was spread across the whole of a 5-letter stimulus when words were identified, whereas it could be focused at the letter level when letter discrimination was required.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, an early theory of word identification subscribed to the idea of a singular "mental lexicon," in which the representations of orthography (spelling), phonology (pronunciation), and semantics (meaning) were all packaged together for words known to the reader (e.g., Treisman, 1960). However, over the last 4 decades, a number of empirical observations in both normal participants and those with acquired brain damage have led a wide range of investigators to suppose that multiple stages of processing are needed to account for lexicalsemantic processing effects (e.g., Becker, 1979;Becker & Killion, 1977;Besner & Smith, 1992;Brown & Besner, 2002;Coltheart, Curtis, Atkins, & Haller, 1993;Coltheart, Rastle, Perry, Langdon, & Zeigler, 2001;Forster & Davis, 1984;Grainger & Jacobs, 1996;McClelland & Rumelhart, 1981;McClelland, 1987;Morton, 1969Morton, , 1979Morton & Patterson, 1980;Neely, 1977Stanners, Jastrembski, & Westbrook, 1975;Stolz & Besner, 1996, 1998; see also Carr & Pollatsek's, 1985, review).…”
Section: Overviewmentioning
confidence: 99%